Republic of Moldova Public Finance Review : Towards More Efficient and More Sustainable Public Finances - World Bank (Washington, DC, 2017)
This report argues that Moldova’s government could reduce fiscal risks to the economy by reducing the size of spending and improving its efficiency, making the tax system simpler, with fewer tax preferences, and strengthening the tax administration. After years of robust performance, in 2015–16 Moldova’s public finances came under pressure. Fraud in the banking sector and economic recession have pushed up public debt, reducing fiscal space and undermining investor confidence. Grants from donors have fallen. Less revenue has forced the government into an ad hoc spending adjustment, with an abrupt reversal of the recent welcome trend of higher capital spending. The government could address these challenges along three dimensions: fiscal stance and sustainability, spending, and revenues. First and foremost, nonetheless, it should concentrate on gradually reducing current spending. As experience in other countries has demonstrated, fiscal consolidation based on spending cuts in a context and circumstances similar to these in Moldova, may yield better results than one based on tax increases. The first dimension to consider is safeguarding fiscal sustainability. The second dimension is reducing the size and improving the efficiency of spending. The third dimension is making the tax system simpler. Moldova collects more revenues than peer countries but also depends on external grants. As in most other Eastern European countries, the revenue structure is skewed toward taxes on goods and services (indirect taxes). Moldova’s tax revenues have been declining as tax exemptions proliferated. While the tax administration has improved, continuing deficiencies in capacity and governance cannot deal with the problem of high informality. Moldova could make the tax system simpler, more efficient, and revenue-enhancing by reducing tax preferences, increasing the nontaxable amount of the personal income tax, improving property valuation, increasing excises, improving tax administration, reducing compliance costs, and simplifying the tax structure. Most importantly, the government needs to deal with tax expenditures, since tax initiatives over the last 15 years resulted in the adoption of a wide range of reduced tax rates and tax exemptions, with significant costs for the budget. In the short term, additional revenues might supplement expenditure cuts to safeguard fiscal sustainability. In the longer term, though, Moldova would need to find substitutes for external grants, so that they gradually become a relatively smaller source of revenues.